(untitled) (Journal of Engineering, 2016)
In this study, the flow and heat transfer characteristics of Al2O3-water nanofluids for a range of the Reynolds number of 3000, 4500, 6000 and 7500 with a range of volume concentration of 1%, 2%, 3% and 4% are studied numerically. The test rig consists of cold liquid loop, hot liquid loop and the test section which is counter flow double pipe heat exchanger with 1m length. The inner tube is made of smooth copper with diameter of 15mm. The outer tube is made of smooth copper with diameter of 50mm. The hot liquid flows through the outer tube and the cold liquid (or nanofluid) flow through the inner tube. The boundary condition of this study is thermally insulated the outer wall with uniform velocity at (0.2, 0.3, 0.4 and 0.5 m/s) at the cold loop and constant velocity at (0.5 m/s) at the hot loop. The results show that the heat transfer coefficient and Nusselt number increased by increasing Reynolds number and particle concentration. Numerical results indicate that the maximum enhancement in Nusselt number and heat transfer coefficient were 9.5% and 13.5% respectively at Reynolds number of 7100 and particles volume fraction of 4%. Results of nanofluids also showed a good agreement with the available empirical correlation at particles volume fractions of 1%, 2% and 3%, but at volume fractions of 4% a slight deviation is obtained.